Application of TBLT in Primary School Classes--A Case Study of theFourth Primary School in Awati County (Asian Education Studies, 2019)
As a national event, education is important issue, which has an influence on thousands of generations. How to teach students to learn knowledge and apply it at the same time has turns out to be a challenging work for numbers of teachers. To solve this problem, some inspiration could come from a method founded in 1980s, which is also called Task Based Language Teaching. As its key characteristics, TBLT makes students learn the knowledge through using the knowledge. In particular, taking execution and communicating interactively are explored as the method to achieve the language learning. This paper investigates the application of the TBLT in the Fourth Primary School in Awati County of Xinjiang. Problems existing in the implementation process are revealed and the underlying causes are analyzed. The results of this study can provide reference for other teachers to use task-based teaching method in the future.